2010
DOI: 10.1074/jbc.m109.079566
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Plasma Proteins as Major Clients for the Extracellular Chaperone Clusterin

Abstract: Clusterin (CLU) is an extracellular chaperone that is likely to play an important role in protein folding quality control. This study identified three deposition disease-associated proteins as major plasma clients for clusterin by studying CLU-client complexes formed in response to physiologically relevant stress (shear stress, ϳ36 dynes/cm 2 at 37°C). Analysis of plasma samples by size exclusion chromatography indicated that (i) relative to control plasma, stressed plasma contained proportionally more soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 77 publications
6
39
0
Order By: Relevance
“…megalin)-mediated endocytosis and lysosomal degradation [51]. This hypothesis is supported by a recent study showing that sCLU in the blood binds to a panel of proteins, including ceruloplasmin, fibrinogen, and albumin, in response to physiologically relevant stress [52].…”
Section: Biochemistry and Functions Of Sclusupporting
confidence: 57%
See 1 more Smart Citation
“…megalin)-mediated endocytosis and lysosomal degradation [51]. This hypothesis is supported by a recent study showing that sCLU in the blood binds to a panel of proteins, including ceruloplasmin, fibrinogen, and albumin, in response to physiologically relevant stress [52].…”
Section: Biochemistry and Functions Of Sclusupporting
confidence: 57%
“…megalin)-mediated endocytosis and lysosomal degradation [51]. This hypothesis is supported by a recent study showing that sCLU in the blood binds to a panel of proteins, including ceruloplasmin, fibrinogen, and albumin, in response to physiologically relevant stress [52].Inside human cells, in addition to nCLU isoform that is mainly localizing in the nucleus and triggers cell death [53], sCLU could redirect to the cytosol under cellular stress [8,54]. In mice, CLU in normal tissues (heart and kidney) is present as a single protein band at approximately 40 kDa in Western blot analysis in our studies [24,55,56], while in cultured cells from these tissues two protein bands at approximately 60 kDa and 40 kDa are detected [24,55,56], suggesting that mouse CLU probably is also retrotranslocated to the cytosol following exposure to sub lethal stress in culture conditions.…”
supporting
confidence: 56%
“…Similarly, shear stress of 40 -60 dynes/cm 2 is physiologically relevant and simulates a degree of the variability present in human circulation: blood is constantly exposed to a variable arterial shear stress ϳ10 -70 dynes/cm 2 in health, although this ranges up to levels greater than 100 dynes/cm 2 in pathological states (71). Similar stresses achieved using similar techniques have been used to demonstrate physiologically relevant chaperone activity in clusterin (5,72).…”
Section: Discussionmentioning
confidence: 67%
“…Inflammation is a state in which many stresses capable of inducing protein misfolding and aggregation are elevated; therefore, it is likely that proteostasis mechanisms will be enhanced during inflammatory events. Moreover, it has been shown that many acute-phase proteins are susceptible to stress-induced misfolding and major endogenous clients for holdase chaperones in human blood plasma (65)(66)(67). To survive periods of increased physiological stress, cells use several different strategies to prevent the accumulation of misfolded proteins (68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%